2017
DOI: 10.1111/aor.12952
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cell‐Activating Substances Using Dialyzers With Various Permeability Profiles

Abstract: Despite multiple efforts to target an improvement in clinical outcomes of patients with end-stage renal disease, several challenges must still be addressed. Dialysis patients are at a high risk for complications, as reflected by increasing mortality rates. The objective of this study is to assess the impact of the application of dialyzers with varying permeability profiles on the removal of cell-activating substances from the blood of hemodialysis (HD) patients. Dialysate samples were collected using Revaclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Agnieszka Latosinska et al of Mosaiques Diagnostics GmbH, Hannover, Germany, reported on the removal of cell‐activating substances from the blood using dialyzers with various permeability profiles. Dialysate samples were collected using Revaclear 400 (RC) and MCO‐Ci400 (MCO‐CI) and the total protein and solute marker concentrations were determined for the concentrated sample.…”
Section: Renal Support and Dialysismentioning
confidence: 99%
See 1 more Smart Citation
“…Agnieszka Latosinska et al of Mosaiques Diagnostics GmbH, Hannover, Germany, reported on the removal of cell‐activating substances from the blood using dialyzers with various permeability profiles. Dialysate samples were collected using Revaclear 400 (RC) and MCO‐Ci400 (MCO‐CI) and the total protein and solute marker concentrations were determined for the concentrated sample.…”
Section: Renal Support and Dialysismentioning
confidence: 99%
“…The method estimated the total condensate output, combining computational fluid dynamics (CFD) of thermal distribution and a simplified 1D model of water vapor saturation of gas. Results showed that condensation rate could vary in a 30-fold range within reasonably small variations of the different variables considered.10 | RENAL SUPPORT AND DIALYSISAgnieszka Latosinska et al102 of Mosaiques Diagnostics GmbH, Hannover, Germany, reported on the removal of cellactivating substances from the blood using dialyzers with various permeability profiles. Dialysate samples were collected using Revaclear 400 (RC) and MCO-Ci400 (MCO-CI) and the total protein and solute marker concentrations were determined for the concentrated sample.…”
mentioning
confidence: 99%
“…More recently, removal of cell-activating substances from uremic blood was investigated in dialysate samples collected during HD with a high-flux membrane and a medium-cut-off membrane (MCO-CI) which has a higher permeability. 29 The latter is a new designed highly porous and selective membrane, characterized by permeability and pore size distribution similar to the kidney itself. 30 Treatment of tubular epithelial cells as an experimental model with the MCO-CI dialysate, as compared to high-flux dialysate, was associated with a significant decrease in cell viability and with loss of brick-like shape of the cell and cell–cell connections.…”
Section: Introductionmentioning
confidence: 99%
“… 30 Treatment of tubular epithelial cells as an experimental model with the MCO-CI dialysate, as compared to high-flux dialysate, was associated with a significant decrease in cell viability and with loss of brick-like shape of the cell and cell–cell connections. 29 The observed phenotype is supported by proteomic analysis (liquid chromatography–MS/MS) coupled with bioinformatics tools, of dialysate samples. Functional classification of proteins overrepresented in samples obtained from HD with MCO-CI revealed the presence of many enzymes (oxidoreductases, transferases, isomerases, and enzyme modulators), signaling molecules, cell adhesion molecules, transfer proteins, immunity proteins, and multiple proteins known to affect tubular epithelial cells’ viability and morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation